FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN ALAT KONTRASEPSI DI WILAYAH KERJA PUSKESMAS ONEMBUTE TAHUN 2021 - Adriani, Fatma (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
The Family Planning program allows couples and individuals to decide freely and responsibly the number of children and spacing they want, how to achieve them, and ensure the availability of safe and effective information and various methods. Contraceptive use tends to increase every year from 2018-2020, as well as in Konawe Regency. Onembute District is one of the districts in Konawe Regency which also experiences an increasing trend of Family Planning participants. In addition, the participation of contraceptive users is still dominated by women, for this reason, research is needed on factors related to the use of contraception in the working area of the Onembute Health Center, Onembute District, Konawe Regency 2021. This research is observational analytical research with a case-kontrol study design. The population in this study is all mothers who use Contraceptives in the working area of Onembute Health Center in July 2021 which amounted to 115 people. The sampling technique in this study used Accidental Sampling. Variabel free in this study is knowledge, attitude and support of the husband while the bound variabel is the use of contraceptives. Data processing is carried out using computer program SPSS, version 26. Data analysis in the form of univariate and bivariate data analysis (using the Chi-Square test). From the results of this study, it can be concluded that there is a meaningful relationship between knowledge, attitudes and support of husbands with the use of contraceptives in the working area of the Onembute Health Center of Konawe Regency in 2021.